Effects of combined resistance training and plyometrics on physical performance in young soccer players - Franco-Marquez, F.; Rodriguez-Rosell, D.; Gonzalez-Suarez, J. M.; Pareja-Blanco, F.; Mora-Custodio, R.; Yanez-Garcia, J. M.; Gonzalez-Badillo, J. J. (International Journal of Sports Medicine, 2015)
This study aimed to determine the effects of combined resistance training and plyometrics on physical performance in under-15 soccer players. One team (n=20) followed a 6-week resistance training program combined with plyometrics plus a soccer training program (STG), whereas another team (n=18) followed only the soccer training (CG). Strength training consisted of full squats with low load (45-60% 1RM) and low-volume (2-3 sets and 4-8 repetitions per set) combined with jumps and sprints twice a week. Sprint time in 10 and 20?m (T10, T20, T10-20), CMJ height, estimated one-repetition maximum (1RMest), average velocity attained against all loads common to pre- and post-tests (AV) and velocity developed against different absolute loads (MPV20, 30, 40 and 50) in full squat were selected as testing variables to evaluate the effects of the training program. STG experienced greater gains (P<0.05) in T20, CMJ, 1RMest, AV and MPV20, 30, 40 and 50 than CG. In addition, STG showed likely greater effects in T10 and T10-20 compared to CG. These results indicate that only 6 weeks of resistance training combined with plyometrics in addition to soccer training produce greater gains in physical performance than typical soccer training alone in young soccer players.